4(3-p)=-5(3p+3)

Simple and best practice solution for 4(3-p)=-5(3p+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3-p)=-5(3p+3) equation:


Simplifying
4(3 + -1p) = -5(3p + 3)
(3 * 4 + -1p * 4) = -5(3p + 3)
(12 + -4p) = -5(3p + 3)

Reorder the terms:
12 + -4p = -5(3 + 3p)
12 + -4p = (3 * -5 + 3p * -5)
12 + -4p = (-15 + -15p)

Solving
12 + -4p = -15 + -15p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '15p' to each side of the equation.
12 + -4p + 15p = -15 + -15p + 15p

Combine like terms: -4p + 15p = 11p
12 + 11p = -15 + -15p + 15p

Combine like terms: -15p + 15p = 0
12 + 11p = -15 + 0
12 + 11p = -15

Add '-12' to each side of the equation.
12 + -12 + 11p = -15 + -12

Combine like terms: 12 + -12 = 0
0 + 11p = -15 + -12
11p = -15 + -12

Combine like terms: -15 + -12 = -27
11p = -27

Divide each side by '11'.
p = -2.454545455

Simplifying
p = -2.454545455

See similar equations:

| 12-20p=-15p | | 10x+9=-1 | | 2t^4+t^3-14t^2+5t+6=0 | | 4y-5+1=6y+8 | | (5-x)+(6-x)=5-x | | X+9=x+3-3+2x | | 2t^4+t^3-14r^2+5t+6=0 | | (-a^3b^5)(9ab^7)= | | 0.00125=-0.025x+0.002 | | -7+x=3(q-5) | | 2x+9=5x+27 | | 2X+10=4X+3 | | 6x-27=77 | | 3(2x-5)=4x+19 | | 1+3x=500 | | 11w+2(3w-1)=-2(3m+3) | | 7(5h-2)=6(6h-1) | | 10+x=7 | | -2u-4=(u+8) | | 5a-8a+10=7a | | 5w+6=9 | | -3(2x+4)=-4x-60 | | 2(x+6)=-(x) | | 3x+10y=2 | | 80y^2-120y+45=0 | | -5600+200x=-2800 | | 49=16t^2+56t | | 2(x+1)-3(x+5)= | | x+37=40 | | 88a^2b^2+24a^2b-32ab^2=0 | | 3x-47+x+7=180 | | x/3+2x-1/7-x-4/21=0 |

Equations solver categories